Representation, equality, and inclusion in deliberative systems: desiderata for a good account. Issue 3 (3rd May 2016) - Erman, Eva
Abstract : What has become known as 'the systemic turn' in the recent literature on deliberative democracy looks like a promising development. However, while much theorizing has been devoted to the question of what a deliberative system may look like, very little has been offered in terms of criteria for what is required for a system to be deliberative democratic. This paper aims to contribute to the systemic approach by setting out a number of desiderata that a satisfactory account of deliberative systems should consider when developing such criteria. This is done by analyzing the main properties of a deliberative system in relation to three essential aspects of democracy: representation, equality, and inclusion. Among other things, it is argued that when theorizing criteria for what a deliberative system requires, a systemic account should carefully distinguish between political and epistemic representation, between political and epistemic equality, and between political and epistemic inclusion.